KESANTUNAN BERBAHASA DALAM DISKUSI PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 3 PETERONGAN - Rohana, Miftakhul; Sulistyowati, Heny (Jurnal Pembelajaran Sastra, 2022)
Humans are social creatures who must always communicate with other people. Language politeness is needed in communicating so that there is no dispute and the message can be received by the interlocutor perfectly. School is the right place to learn language politeness. The discussion technique is an appropriate technique for practicing language politeness, students are trained to dare to appear or speak in public, are trained to hold back (hold emotions), are trained to respect or respect others. This study aims to describe language politeness in discussions on learning Indonesian at SMP Negeri 3 Peterongan. The subject of this research is class 9G students who are male and come from all over Indonesia because the subject lives in a boarding school. This study uses a qualitative descriptive technique. Data were obtained from recordings during class discussions on learning Indonesian. The recording results are transcribed and reduced as needed. The data is tabulated and then analyzed. The conclusion obtained from the results of the analysis (based on Leech's theory) is that politeness in language in discussions on learning Indonesian at SMP Negeri 3 Peterongan has been applied by students.. Students have used the maxims of wisdom, simplicity, generosity, appreciation, agreement, and sympathy.